Cryptological properties of multi-output rotation symmetric functions - YUAN Yan-bin; ZHAO Ya-qun (Tongxin xuebao)
The notion of multi-output rotation symmetric functions was introduced.Firstly, the properties of generalized Walsh spectrum and the generalized autocorrelation functions were presented.Then by constructing matrixes, some necessary and sufficient conditions were given for this class of functions to satisfying cryptological properties of balancedness, correlation immunity and so on.Especially, it presented a necessary and sufficient condition to fulfilling 1st order correlation immunity.At last, when n was odd number, the matrixes of n variables multi-output Plateaued rotation symmetric functions had special properties, so a method was introduced to find the odd number variables multi-output Plateated rotation symmetric functions.And this method only need calculate part of the generalized Walsh cycle spectrum, and the calculation could be reduced by almost half of the amount.